Understanding the thermal benefits of retrofitting 'living walls' to existing buildings. Issue 2 (May 2022) - Fox, Matthew; Murphy, Tom
Abstract : Like green roofs, 'living walls' offer many environmental, social and economic benefits. Matthew Fox and Tom Murphy of The University of Plymouth report on a study of one of the campus buildings, which proved that a living wall can improve thermal insulation by nearly a third.